Flipping the mJOA: Clinical utility of the modified Japanese Orthopaedic Association score as a tool for detecting degenerative cervical myelopathy - Caroline Treanor; Conor Gallagher; Warren Lenehan; Hannah Gantly; Ciaran Bolger; Ailish Malone (Brain and Spine)
Introduction: People with Degenerative Cervical Myelopathy (DCM) often experience diagnostic delay. This could lead to poorer outcomes, including disability. Research question: Does the modified Japanese Orthopaedic Association scale (mJOA) have clinical utility as an early detection tool for possible DCM? Materials and methods: This is a prospective study of consecutive adult patients, referred to a National Neurosurgical Centre with a neck problem. Assessing clinicians undertook standard clinical examination and calculated the mJOA score. A consultant radiologist independently reported radiological findings, after which the assessing clinician determined the diagnosis. The sensitivity and specificity of mJOA for DCM at various cut-points was statistically analysed using Receiver Operating Characteristics (ROC) curves. Results: Of 201 patients (98 male, mean age 52.6 ± 13y) assessed over 13 months, 21 were diagnosed with DCM (prevalence 10.4%). Fifteen (71.4%) had a mJOA score classifying disease severity as mild, 4/21 (19%) had moderate disease and two (9.5%) had severe disease. A mJOA score ≤17 (cutpoint ≥1) showed sensitivity of 95% and specificity of 71% for the clinical diagnosis of DCM. mJOA score ≤16 (cutpoint ≥2) had sensitivity of 62% and specificity of 90%. The ROC area under the curve was 0.885 (95% confidence interval: 0.82 to 0.95). 87% of patients were correctly classified. Discussion and conclusion: mJOA score ≤16 is 90% specific for a subsequent diagnosis of DCM in people with neck problems and has potential to be used as an early detection tool. Further research is needed to replicate these findings and establish feasibility and acceptability in primary care.